Cambio Climático y Fiscalización Ambiental: Regulación de Emisiones de las Actividades Minero energéticas - Aldana Durán, Martha Inés (2014)
The author develops the main tenets of Three Dimensional Theory of law and its particular application to the field of climate change. In this context, the relevant behaviors on climate change, the values that are seeking to achieve through regulation of does these behaviors, and national and international standards are presented. In addition, he does special emphasis on the identification of active behaviors relating to the issuing agent of greenhouse gases (GHGs), which for the purposes of the activities responsible for the emission of these gases in our country have done. Consequently, by reference, the main contents of Mexican law are presented on climate change legislation that affects the obligation to report GHG emissions data to the agents that generate them. Finally, suggestions are made in order to implement the climate commitment in mining and energy activities.